A practical guide to the interpretation of PK/PD profiles of longer-acting analogue insulins. Part one: The principles of glucose clamp studies. Issue 1 (2nd January 2018) - Greeff, Oppel BW; van Tonder, Jacob John; Naidu, Kershlin; McMaster, Alicia; van Tonder, Alet; Mothilal, Rashem
Abstract: Glucose clamp studies are used to determine pharmacokinetics (PK) and pharmacodynamics (PD) of analogue insulins. With the development of longer-acting basal analogue insulins, including glargine 300 (Gla-300) and insulin degludec (IDeg), results from numerous glucose clamp studies are readily available. However, interpreting PK/PD profiles in a scientifically sound manner can be a challenging feat. This is the first in a series of publications that will suggest practical tips for interpreting and comparing results from glucose clamp studies. Variations in the glucose clamp methodology, duration of clamp studies and glucose clamp targets influence the study design and results significantly. Selection of study populations, including healthy patients or patients with Type 1 or 2 diabetes mellitus, has important implications. The dose of study insulin should reflect that of the general treatment population, and ideally steady-state conditions should be used. During the study the plasma insulin concentration and glucose infusion rate describe the pharmacokinetics and pharmacodynamics of the study insulin. With these practical tips in mind, results of glucose clamp studies can be interpreted in a scientifically correct manner. The next article in this series will discuss the interpretation of PK/PD profiles using two newly developed longer-acting basal analogue insulins: Gla-300 and IDeg.